Modification of turbulent dissipation rates by a deep Southern Ocean eddy - Sheen, KL; Brearley, JA; Naveira Garabato, AC; Smeed, DA; Laurent, LS; Meredith, MP; Thurnherr, AM; Waterman, SN (Geophysical Research Letters, 2015)
This is the final version. Available from AGU via the DOI in this record All data used in this study are available by communication with the author and will be archived at British Oceanographic Data Centre The impact of a mesoscale eddy on the magnitude and spatial distribution of diapycnal ocean mixing is investigated using a set of hydrographic and microstructure measurements collected in the Southern Ocean. These data sampled a baroclinic, middepth eddy formed during the disintegration of a deep boundary current. Turbulent dissipation is suppressed within the eddy but is elevated by up to an order of magnitude along the upper and lower eddy boundaries. A ray tracing approximation is employed as a heuristic device to elucidate how the internal wave field evolves in the ambient velocity and stratification conditions accompanying the eddy. These calculations are consistent with the observations, suggesting reflection of internal wave energy from the eddy center and enhanced breaking through critical layer processes along the eddy boundaries. These results have important implications for understanding where and how internal wave energy is dissipated in the presence of energetic deep geostrophic flows. DIMES is supported by the Natural Environment Research Council (NERC) grants NE/E007058/1 and NE/E005667/1 and U.S. National Science Foundation grants OCE‐1231803, OCE‐0927583, and OCE‐1030309. K.L.S. and J.A.B. are supported by NERC.